Central Bank Independence and the Conduct of Monetary Policy in the United Kingdom - Samiei, Hossein; Martijn, Jan. (Washington, D.C. : International Monetary Fund, 1999)
The U.K. monetary policy framework, which combines inflation targeting with operational independence, provides a suitable arrangement for focused and credible monetary policy. However, potential weaknesses could result from features that have not yet been fully tested: the credibility and transparency of the inflation forecasts, which form the core of policy decisions, have diminished as a result of independence; and the framework could encourage excessive activism and frequent changes in interest rates. Although policy coordination could also suffer from independence, the new partly rules-based fiscal and monetary regimes will promote overall macroeconomic stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet